Estimating soil hydraulic properties using mini disk infiltrometer. Issue 1 (2nd January 2019) - Naik, Aparimita Priyadarshini; Ghosh, Biplab; Pekkat, Sreeja
ABSTRACT: Characterizing soil hydraulic properties of the unsaturated zone is mandatory for reliable modeling of flow process and effective flood/drought modeling. The objective of this study is to evaluate infiltration characteristics of an area comprising of four different types of soils, namely, sand, loamy sand, loam and silt. A handy mini disk infiltrometer was used to determine cumulative infiltration based on which near saturated hydraulic conductivity values were determined. To verify its accuracy, simulations were carried out in HYDRUS 2D/3D which solves Richard's equation by using Van Genuchten's model. It is found that for loamy sand soil HYDRUS is giving quite appreciable results. However, for sandy and loamy soil, the numerically simulated results are underestimated whereas for silt soil the simulated results are overestimated when compared with the experimental results. This variability is mainly due to the variation in the parameters used for numerical simulation. Therefore, an inverse simulation was carried out using HYDRUS for getting the optimized values of the hydraulic parameters. Model performance is assessed by different statistics, such as correlation coefficient, the root mean square error, and the Nash-Sutcliffe efficiency index. HYDRUS is a software package for simulating water, heat, and solute movement in two- and three-dimensional variably saturated media. The software package consists of a computational computer program and an interactive graphics-based user interface.